Health Inequality and Development 2011
DOI: 10.1057/9780230304673_5
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Determinants of Child Mortality in Kenya

Abstract: This paper focuses on the determinants of infant and child mortality in Kenya. It specifically examines how infant and child mortality is related to the household's environmental and socio-economic characteristics, such as mother's education, source of drinking water, sanitation facility, type of cooking fuels and access to electricity. A hazard rate framework is used to analyze the determinants of child mortality. Duration models are easily applicable to the problem of child mortality as this class of models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
36
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 11 publications
9
36
1
1
Order By: Relevance
“…According to World Bank (2010), environmental risk factors were estimated to account for about one-fifth of the total burden of disease in low income countries. The WHO (2002) similarly, reported in Mutunga (2007) that among the ten identified leading mortality risks in high mortality developing countries, unsafe water, sanitation and hygiene ranked second while smoke from solid fuels ranked fourth. Kumar and File (2005) The study concluded that an increase in Mothers' education and improved health care services are significant in reducing child mortality in Ethiopia.…”
Section: Empirical Frameworkmentioning
confidence: 99%
“…According to World Bank (2010), environmental risk factors were estimated to account for about one-fifth of the total burden of disease in low income countries. The WHO (2002) similarly, reported in Mutunga (2007) that among the ten identified leading mortality risks in high mortality developing countries, unsafe water, sanitation and hygiene ranked second while smoke from solid fuels ranked fourth. Kumar and File (2005) The study concluded that an increase in Mothers' education and improved health care services are significant in reducing child mortality in Ethiopia.…”
Section: Empirical Frameworkmentioning
confidence: 99%
“…Sanitation is the most important factor for the reduction of the main killers of children like diarrheal diseases [40]. The source of water in any community is always a crucial predictor of the persisting sanitary conditions in that particular community [41,42]. Good source of drinking water is essential for both provisions of good prenatal and postnatal and is necessary for a child's health [6].…”
Section: Discussionmentioning
confidence: 99%
“…Suivant le schéma explicatif proposé par Mosley et Chen (1984) et par rapport aux données disponibles, on peut classer les variables explicatives en deux catégories (Madise, Banda et Benaya (2003), Mutunga (2007)). Dans le premier groupe, les variables socio-économiques suivantes ont été retenues :…”
Section: Les Déterminants De La Mortalité Des Enfantsunclassified